Organocatalytic tandem three-component reaction of aldehyde, alkyl vinyl ketone, and amide: one-pot syntheses of highly functional alkenes - Wang, De-Wei; Syu, Siang-en; Hung, Yi-Ting; Chen, Pei-yi; Lee, Chia-Jui; Chen, Ko-Wei; Chen, Yu-Jhang; Lin, Wenwei (Organic & biomolecular chemistry, 2011)
An EtPPh2-or PPh3-catalyzed tandem three-component reaction of aldehyde, alkyl vinyl ketone, and amide is developed. Its further application in one-pot syntheses of highly functional alkenes starting from aldehydes, alkyl vinyl ketones, and amides is realized. A wide variety of highly functional alpha,beta-unsaturated ketones can be furnished in 68-99% yields with high stereoselectivity (E/Z up to 98 : 2) within overall 3-29.5 h.